2000
DOI: 10.1038/sj.ejcn.1601078
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake and growth of infants in Iceland—a population with high frequency of breast-feeding and high birth weight

Abstract: Objective: To investigate infants' energy intake and growth in a population with a high frequency of breastfeeding and high birth weight. Design: The infants' consumption was recorded once a month from 1 to 12 months of age. At the ages of 2, 4, 6, 9 and 12 months all ingested food was weighed accurately to calculate nutrient intake. A control group participated at the age of 9 months. Setting: Participants, who were born healthy, were recruited from four different maternity wards. Growth data were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
3
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 22 publications
7
80
3
6
Order By: Relevance
“…Wharf et al (1997) reported higher iron stores in girls than boys, concluding that it could possibly reflect the faster absolute growth rate of boys than girls. This difference in growth between the genders disappears in the study population when incremental growth was calculated as a ratio of birth size (Atladottir & Thorsdottir, 2000), hence, the difference in iron status between the genders cannot be explained by growth difference alone. This is supported by Domellof et al (2002), which concluded that gender difference in MCV and serum ferritin values in infancy might be due to genetic and hormonal factors rather than differences in growth rate.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Wharf et al (1997) reported higher iron stores in girls than boys, concluding that it could possibly reflect the faster absolute growth rate of boys than girls. This difference in growth between the genders disappears in the study population when incremental growth was calculated as a ratio of birth size (Atladottir & Thorsdottir, 2000), hence, the difference in iron status between the genders cannot be explained by growth difference alone. This is supported by Domellof et al (2002), which concluded that gender difference in MCV and serum ferritin values in infancy might be due to genetic and hormonal factors rather than differences in growth rate.…”
Section: Discussionmentioning
confidence: 89%
“…The participants were randomly assigned to each group. There were no major differences between the control group and the study group, suggesting that participation in the longitudinal study did not affect the dietary intake (Atladottir & Thorsdottir, 2000). In this population of high economic standard the parents provided information about socio-economic variables, such as their age, education, occupation, smoking status, family income and the number of siblings.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations